Pengaruh Pendapatan Asli Daerah Dan Dana Alokasi Umum terhadap Kemandirian Daerah dan Pertumbuhan Ekonomi Daerah - Afrizal Tahar; Maulida Zakhiya (Journal of Accounting and Investment, 2011)
The purposes of this research is to verify, firstly what is the Local Government Revenue (PAD) has positive impact toward regional sufficiency, and what is the General Allocation Fund (DAU) has negative impact toward regional independent. Secondly, what is the Local Government Revenue (PAD) and General Allocation Fund (DAU) that is supported by regional independent will give good influence toward the economic growth. The research method in this thesis is to use purposive sampling method, with a total sample of 36 districts/cities each yearfrom 56 districts/cities in Kalimantan Island. This research was done from 2003 to 2008. The data was got from the Central Statistical Agency (BPS) and the site of Directorate General of Fiscal Balance (www.djpk.depkeu.go.id). The data that is analyzed prepared from Consolidated Actual Revenues and Expenditures Budget (APBD) and the Growth Rate Data (PDRB). From the result of research indicates the Local Government Revenue (PAD) has positive and significant impact toward regional independent, the General Allocation Fund (DAU) has negative impact toward regional independent. While, the Local Government Revenue (PAD) and General Allocation Fund (DAU) that is supported by regional independent do not have significant impacttoward the economic growth.